Cutaneous larva migrans with bullous eruptions in a young child - Jamani, Nurjasmine Aida; Hashim, Hazwani Hanum (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2022)
Infection of cutaneous larva migrans is usually acquired in the tropical region and mainly affects children. It is generally diagnosed with symptoms of severe itchiness and skin lesion that appears as a migrating erythematous linear lesion. It often occurs with a history of skin exposure to soil. Atypical presentation of the infection causes difficulty in diagnosis and delays treatment for the patient. Once diagnosed, cutaneous larva migrans is treated easily with helminth medications such as albendazole. Recognition of the skin lesion of cutaneous larva migrans in the atypical presentation of the infection for prompt treatment will comfort and prevent secondary infection complications. This case describes a presentation of bullous eruption in a child infected with cutaneous larva migrans.